Advances of microfluidic lung chips for assessing atmospheric pollutants exposure - Wang, Hui; Yin, Fangchao; Li, Zhongyu; Su, Wentao; Li, Dong (Environment international, 2023)
[Display omitted] •An up-to-the-date review summarizes the key features of lung chips.•Current trends in the fabrication of lung chips.•Recent progresses in the application of lung chip to assess air pollutants exposure.•Current challenges and future opportunities of lung chip development. Atmospheric pollutants, including particulate matters, nanoparticles, bioaerosols, and some chemicals, have posed serious threats to the environment and the human’s health. The lungs are the responsible organs for providing the interface betweenthecirculatory system and the external environment, where pollutant particles can deposit or penetrate into bloodstream circulation. Conventional studies to decipher the mechanismunderlying air pollution and human health are quite limited, due to the lack of reliable models that can reproduce in vivo features of lung tissues after pollutants exposure. In the past decade, advanced near-to-native lung chips, combining cell biology with bioengineered technology, present a new strategy for atmospheric pollutants assessment and narrow the gap between 2D cell culture and in vivo animal models. In this review, the key features of artificial lung chips and the cutting-edge technologies of the lung chip manufacture are introduced. The recent progresses of lung chip technologies for atmospheric pollutants exposure assessment are summarized and highlighted. We further discuss the current challenges and the future opportunities of the development of advanced lung chips and their potential utilities in atmospheric pollutants associated toxicity testing and drug screening.